Analysis, design and implementation of a low-power low-voltage audio class D amplifier with feedback - Lon, Yong Seng. (2008)
This dissertation describes the theoretical and practical work into analysis, design and implementation of a closed-loop (negative feedback) low-power low-voltage audio Class D amplifier. The primary objective is to obtain improved performance (compared to an open-loop Class D amplifier) in the important parameters, including distortion, gain linearity and zero-input duty cycle error.